PSIKOEDUKASI KELOMPOK KADER KESEHATAN JIWA (K3J) DALAM PEMBERDAYAAN PENDERITA SKIZOFRENIA DI MASYARAKAT DI KELURAHAN PEDUNGAN – DENPASAR SELATAN - I Gusti Ayu Rai Rahayuni (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
The purpose of this pre experimental study is to examine the effect of the mental health volunteer psycho-education program on mental health volunteer caregivers’ attitude to provide rehabilitation for patients with schizophrenia in community. The attitude in this study includes cognitive, affective and behavioral components. The subjects were the mental health volunteer of schizophrenia patients. The samples were a group of 18 participants who receive 5 sessions of the intervention. The activities in the intervention included building of working alliance, introducing about schizophrenia, caring and rehabilitation strategies, coping mechanism and problem solving strategies by methods of sharing experience, discussion and role play. Attitudes towards schizophrenia questionnaire for relatives were used to assess the families’ attitude. Data analyses used was paired t-test. The finding that mental health volunteer caregivers who participated in this program were reported the improvement of their attitude after receiving the intervention (p < .05). The present intervention had a significant influence to increase mental health volunteer caregivers' attitude including affective, cognitive and behavioral to provide rehabilitation for patients with schizophrenia based on religion approach. The practitioners need to continue and extend the program based on the Balinese culture in larger samples and areas by using booklet that was used in this study as a guideline to increase the mental health volunteer’ attitude toward the better prosedure to provide rehabiliation of the schizophrenia patients that can increasing their quality of life in community.